Corporate political connections and the 2008 Malaysian election. (May 2015) - Fung, Simon Y.K.; Gul, Ferdinand A.; Radhakrishnan, Suresh
Abstract: We examine whether the relationship between political connections and firm value is moderated by the length of time firms have been politically connected. We find that compared to firms with political connections for a short period, firms with political connections for a long period have a smaller magnitude of negative stock price reaction to the 2008 General Election loss of the supermajority by the ruling party in Malaysia. We also find that the smaller magnitude of negative stock price reaction is, in part, attributable to improvements in board of director characteristics. Furthermore, we find that while the performance subsequent to the General Election of politically connected firms is worse than that of non-politically connected firms, firms with political connections for a long period exhibit better performance than those connected for short periods. Collectively, the evidence shows that the length of political connections is an important factor that moderates economic value.